Pobreza y migraciones en una ciudad intermedia argentina. Una mirada desde la historia (Neuquén, 1980) - Perren, Joaquín (El Colegio de México A.C., 2015)
This article seeks to examine the links between poverty and migrations in Neuquén (Patagonia, Argentina) in the early 1980s. In methodological terms, this study uses the information provided by the National Population and Housing Census by census division. At the same time, and in order to detail many of the phenomena analyzed, thematic mappings are presented, which were drawn up using geographical information systems, particularly the ArcView gis 3.3 program.